Strategi Pengendalian Perkembangan Permukiman Disepanjang Sungai Tallo Kelurahan Rapokalling Kecamatan Tallo Kota Makassar - Ariadi Abil; Rudi Latief; Ilham Yahya (Journal of Urban Planning Studies, 2020)
The purpose of this study is to identify the causes that lead to the development of settlements along the banks of the Tallo River, Rapokalling Village, Tallo District, Makassar City. And to identify control strategies for settlement ty. And to find out the strategy for controlling the development of settlements along the banks of the Tallo River, Rapokalling Village, Tallo District, development along the Tallo River, Rapokalling Village, Tallo District, Makassar City. To find out the causes that led to the development of settlements along the banks of the Tallo River, Rapokalling Village, Tallo District, Makassar CiMakassar City. The variables used consisted of four of them: (1) Political Aspects; (2) Economic Aspects; (3) Social Aspects; (4) Cultural Aspects; The analytical method used is in the form of chi-square analysis, then the contingency test is used in drawing conclusions, which is followed by a Likert scale scoring system as a parameter to determine the size of the relationship between the X variable and Y. Next, develop a control strategy for settlement development along the banks of the Tallo River, Rapokalling Village, Tallo City District Makassar with the SWOT analysis method.